Microdiversity of Enterococcus faecalis isolates in cases of infective endocarditis: selection of non-synonymous mutations and large deletions is associated with phenotypic modifications. Issue 1 (1st January 2021) - Royer, G.; Roisin, L.; Demontant, V.; Lo, S.; Coutte, L.; Lim, P.; Pawlotsky, J. M.; Jacquier, H.; Lepeule, R.; Rodriguez, C.; Woerther, P. L.
ABSTRACT: Context : Today, infective endocarditis (IE) caused by Enterococcus faecalis represents 10% of all IE and is marked by its difficult management and the frequency of relapses. Although the precise reasons for that remain to be elucidated, the evolution of the culprit strain under selective pressure through microdiversification could be, at least in part, involved. Material and methods : To further study the in situ genetic microdiversity and its possible phenotypic manifestations in E. faecalis IE, we sequenced and compared multiple isolates from the valves, blood culture and joint fluid of five patients who underwent valvular surgery. Growth rate and early biofilm production of selected isolates were also compared. Results : By sequencing a total of 58 E. faecalis genomes, we detected a considerable genomic microdiversity, not only among strains from different anatomical origins, but also between isolates from the same studied cardiac valves. Interestingly, deletions of thousands of bases including the well-known virulence factors ebpA/B/C, and srtC, as well as other large prophage sequences containing genes coding for proteins implicated in platelet binding (PlbA and PlbB) were evidenced. The study of mutations helped unveil common patterns in genes related to the cell cycle as well as central metabolism, suggesting an evolutionary convergence in these isolates. As expected, such modifications were associated with a significant impact on the in-vitro phenotypic heterogeneity, growth, and early biofilm production. Conclusion : Genome modifications associated with phenotypic variations may allow bacterial adaptation to both antibiotic and immune selective pressures, and thus promote relapses.